Evaluation of the relationship between serum lactate level and Base Deficit with the prognosis of burns in patients with severe burns - Behzad Zohrevandi; Mahan Azizzade Dobakhshari; Seyyed Mahdi Zia Ziabari; Ehsan Kazemnejhad-Leili; Jafar Saberi; Siamak Rimaz (مجله دانشگاه علوم پزشکی گیلان, 2025)
Background: In recent years, plasma base deficit (BD) has gained attention as a suitable marker for evaluating blood flow and predicting outcomes in burn patients. Objective: The aim of this study is to determine whether serum lactate levels and base deficit can be used as prognostic tools for mortality among patients with burn injuries. Methods: This analytical cross-sectional study was conducted on 389 patients with burns of 20% or more. Blood samples were collected to measure BD and serum lactate levels, repeated every 12 hours during the first 48 hours of hospitalization. Demographic information and hospitalization details were recorded in a collection form, and all data were entered into SPSS version 21 for statistical analysis. Results: The average age of the patients was 32 years, and most of them were male. The results indicated that serum lactate levels were significantly higher in deceased patients compared to those who improved (P<0.001), and BD was significantly lower in the deceased group (P<0.001). The best cutoff points for serum lactate at the third hour were 4.5, with a sensitivity of 96.9% and specificity of 95%. For bicarbonate at the second hour, the cutoff was -3.25, with a specificity of 96% and sensitivity of 94%. On the second day, the cutoff for bicarbonate was 4.5, with a sensitivity of 98.6% and specificity of 87%. Conclusion: This study indicates that measuring BD and serum lactate levels can be valuable tools in the assessment and management of burn patients. Additionally, the determined cutoff points for BD may be useful in triaging burn patients.